2010
DOI: 10.1186/1471-2202-11-44
|View full text |Cite
|
Sign up to set email alerts
|

N-arachidonoyl glycine, an abundant endogenous lipid, potently drives directed cellular migration through GPR18, the putative abnormal cannabidiol receptor

Abstract: BackgroundMicroglia provide continuous immune surveillance of the CNS and upon activation rapidly change phenotype to express receptors that respond to chemoattractants during CNS damage or infection. These activated microglia undergo directed migration towards affected tissue. Importantly, the molecular species of chemoattractant encountered determines if microglia respond with pro- or anti-inflammatory behaviour, yet the signaling molecules that trigger migration remain poorly understood. The endogenous cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
316
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 277 publications
(333 citation statements)
references
References 65 publications
9
316
3
Order By: Relevance
“…CB 1 receptors are found mostly within the nervous system (Matsuda et al, 1990), whereas CB 2 receptors predominate outside of the nervous system (Munro et al, 1993). G protein-coupled receptor 18 (GPR18) (McHugh et al, 2010), G protein-coupled receptor 55 (GPR55) (Hiley and Kaup, 2007), and G protein-coupled receptor 119 (GPR119) (Overton et al, 2006) are also receptors that can be activated by endogenous cannabinoids, but they have been much less studied than CB 1 and CB 2 receptors. With respect to PD and LID, studies have focused on modulation of CB 1 receptors, which are abundant within the basal ganglia (Pacher et al, 2006), where they can modulate release of glutamate and GABA (Howlett et al, 2002).…”
Section: A Cannabinoid Receptorsmentioning
confidence: 99%
“…CB 1 receptors are found mostly within the nervous system (Matsuda et al, 1990), whereas CB 2 receptors predominate outside of the nervous system (Munro et al, 1993). G protein-coupled receptor 18 (GPR18) (McHugh et al, 2010), G protein-coupled receptor 55 (GPR55) (Hiley and Kaup, 2007), and G protein-coupled receptor 119 (GPR119) (Overton et al, 2006) are also receptors that can be activated by endogenous cannabinoids, but they have been much less studied than CB 1 and CB 2 receptors. With respect to PD and LID, studies have focused on modulation of CB 1 receptors, which are abundant within the basal ganglia (Pacher et al, 2006), where they can modulate release of glutamate and GABA (Howlett et al, 2002).…”
Section: A Cannabinoid Receptorsmentioning
confidence: 99%
“…PAM, an enzyme with a well-defi ned role in ␣ -amidated peptide biosynthesis ( 38 ), has been suggested to catalyze N -fatty acylglycine cleavage in vivo. A number of N -fatty acylglycines have been identifi ed from mammalian sources ( 37,39 ), and there is evidence that these members of the fatty acid amide family are also cell signaling lipids (40)(41)(42). The biosynthesis of these lipids is also unclear; suggested pathways include glycine conjugation of the fatty acyl-CoA thioesters ( 34,43 ) and sequential oxidation of the N -acylethanolamines ( 44,45 ) ( Fig.…”
Section: Use Of Bsa As a Fatty Acid Carriermentioning
confidence: 99%
“…Several novel cannabinoid receptors, including G protein-coupled receptor 18 (GPR18), mediate diverse cardiovascular effects (OffertĂĄler et al, 2003;Kohno et al, 2006;McHugh et al, 2010). Our recent findings (Penumarti and Abdel-Rahman, 2014) demonstrated GPR18 expression in rostral ventrolateral (RVLM) neurons, which modulate the sympathetic activity (Sved et al, 2003;Kishi et al, 2004;Guyenet, 2006), and suggested a restraining influence for RVLM GPR18 on blood pressure (BP).…”
Section: Introductionmentioning
confidence: 96%